Literature Review on Siddha Medicine for the Management of Neerkana Maantham with Utthamani Kudineer- A Drug Review - Santhi.S,; Amala Hazel.A.M,; Meenakshi Sundaram.M,; Meenakumari.R, (International Journal of Ayurveda and Pharma Research, 2021)
Siddha medicine is an ancient and traditional system of medicine.. When the three humors (Vatham, Pitham, Kabam) are in proper balance then the person experiences good health; any imbalance of three humors leads to disease. Acute Nasopharyngitis defines an inflammation of the mucous membrane of the naso pharynx. It is characterized by rhinorrhea, nasal obstruction, sneezing, malaise, fever, headache, & myalgia. It may be correlated with Neerkana maantham, one of the 31 types of Maantham in children mentioned in Siddha literature Balavagadam. The symptoms of Neerkana mantham can be managed by Siddha herbal formulation Utthamani kudineer. The main ingredients of the Utthamani kudineer are Chukku, Milagu, Thippili, Omam, Sutta Vasambu, Utthamani leaf, Velai ver, Nochi thulir, Murungai eerku, Nuna eerku. The ingredients of this formulation possess anti-inflammatory, antiviral, anti microbial, antipyretic activities. All the ingredients of trial drug are purely herbals only. It is easily prepared, palatable, assimilates quickly and also safe for pediatric usage in the treatment of Neerkana maantham. Hence, this article gives an insight on the efficacy of Utthamani kudineer for Neerkana maantham (Acute Nasopharyngitis) based on review of various literatures and scientific studies. This review further focuses to improve the research on Siddha herbal medicines.